Contributory Negligence In Fatal Accident Claims - Balan, P (Journal of Malaysian and Comparative Law, 1999)
A bane of our modern society, and a matter which causes considerable concern and anxiety, is the ever increasing number of fatal accidents, particularly fatal accidents from motor vehicle collisions.